Lithium-rich manganese-based material, preparation method of lithium-rich manganese-based material, positive pole piece, battery and electric device

By introducing Mg and NB doping and Linbo3 coverage in the introduction of lithium -rich manganese -based positive materials, the material's lack of low -temperature room temperature multiplier performance is solved, and higher electrochemical performance and better preparation process are achieved.

CN119361670APending Publication Date: 2025-01-24GREE ALTAIRNANO NEW ENERGY INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411221864.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have poor performance in low temperature and room temperature magnification performance, and traditional synthesis methods have problems with uneven particle size distribution and wastewater generation.

Method used

The lithium -rich manganese -based material with a nuclear shell structure. The kernel materials are doped by MG and NB, and the shell is covered by Linbo3 to improve the electrochemical properties of the material through combustion method.

Benefits of technology

Significantly improve the battery's low-temperature performance per gram capacity and room temperature rate performance per gram capacity, improve the particle size and discharge efficiency of the material, and enhance the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005023269850000071
    Figure BDA0005023269850000071
  • Figure BDA0005023269850000081
    Figure BDA0005023269850000081
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses a lithium-rich manganese-based material, a preparation method thereof, a positive pole piece, a battery and an electric device. The lithium-rich manganese-based material has a core-shell structure, the core material comprises a material with a chemical formula of Li (1.2-x) Mg < x > Ni (0.17-y) Nb < y > Co < 0.16 > Mn < 0.47 > O < 2 >, x is equal to 0.05-0.1, and y is equal to 0.05-0.07; and the material of the shell comprises LiNbO3. The modified lithium-rich manganese-based composite material is prepared through a combustion method and is coated with a fast lithium ion conductor LiNbO3, meanwhile, an inner core material is doped with Mg and Nb, and the prepared lithium-rich manganese-based material can remarkably improve the gram volume of a battery in a low-temperature state and the gram volume of the battery under room-temperature rate capability; meanwhile, the particle size, gram volume and discharge efficiency of the lithium-rich manganese-based material can be improved, and the electrochemical performance of the battery is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a lithium-rich manganese-based material and a preparation method thereof, as well as a positive electrode sheet, a battery and an electrical device. Background Art

[0002] The performance of lithium-ion batteries depends largely on the cathode material. At present, commercial cathode materials include LiCoO2, LiMn2O4, LiFePO4 and ternary materials, etc. Their actual specific capacity is basically less than 200mAh / g. x Co y Mn z Compared with traditional materials, O2·(1-a)Li2MnO3 (x+y+z=1, 0<a<1) has the characteristics of high specific energy (300Wh / kg), low cost, environmental friendliness, and a new charge and discharge mechanism (Li2O is released at the platform of 4.5V in the first charge curve). The specific capacity in the voltage range of 2.0-4.8V is greater than 200mAh / g, making it a hot topic of research.

[0003] At present, the synthesis methods of lithium-rich layered cathode materials mainly include solid phase method and coprecipitation method. Although the synthesis process of solid phase method is relatively simple, the particle size distribution of the product is uneven, resulting in poor electrochemical performance. 1.2 Ni 0.17 Co 0.16 Mn 0.47 The discharge capacity of O2 material is relatively low. The coprecipitation-sintering method is used to remove impurity ions (such as Na + and SO4 2- The co-precipitated material needs to be washed repeatedly, which will cause material loss and generate a large amount of waste water during the production process. Summary of the invention

[0004] In view of this, the purpose of the present application is to provide a lithium-rich manganese-based material and a preparation method thereof, so that the modified lithium-rich manganese-based material can significantly improve the low-temperature performance gram capacity and room temperature rate performance gram capacity;

[0005] Another object of the present application is to provide a positive electrode sheet, a battery and an electrical device based on the above-mentioned lithium-rich manganese-based material.

[0006] In order to solve the above technical problems / achieve the above objectives or at least partially solve the above technical problems / achieve the above objectives, as a first aspect of the present application, a lithium-rich manganese-based material is provided, having a core-shell structure, wherein the core material comprises a chemical formula of Li 1.2-x Mg x Ni 0.17-y Nb yCo 0.16 Mn 0.47 O2 material, x=0.05-0.1, y=0.05-0.07; shell material includes LiNbO3.

[0007] Optionally, the shell material has a thickness of 2-6 nm.

[0008] As a second aspect of the present application, a method for preparing the lithium-rich manganese-based material described in the present application is provided, comprising:

[0009] The raw materials of lithium source, magnesium source, nickel source, first niobium source, cobalt source and manganese source are weighed according to the stoichiometric ratio of the core material, fuel is added and mixed evenly, and then high temperature treatment is performed to obtain a pre-burned product;

[0010] The pre-burned product is ball-milled with a raw material of a second niobium source dissolved in a solvent, dried, and then calcined at a high temperature to obtain the lithium-rich manganese-based material.

[0011] Optionally, the lithium source includes lithium carbonate, lithium acetate, lithium nitrate, and one or more of their hydrates; the magnesium source includes magnesium carbonate, magnesium hydroxide, magnesium acetate, magnesium nitrate, magnesium oxide, and one or more of their hydrates; the nickel source includes nickel acetate, nickel nitrate, nickel hydroxide, and one or more of their hydrates; the first niobium source and the second niobium source independently include niobium oxide, ammonium niobium oxalate, and one or more of their hydrates; the cobalt source includes cobalt acetate, cobalt nitrate, cobalt hydroxide, and one or more of their hydrates; the manganese source includes manganese acetate, manganese nitrate, manganese hydroxide, and one or more of their hydrates.

[0012] Optionally, the fuel comprises urea.

[0013] Optionally, the high temperature treatment includes heat preservation treatment at 120-600°C; and the high temperature calcination includes high temperature calcination at 900-950°C.

[0014] As a third aspect of the present application, a positive electrode plate is provided, comprising the lithium-rich manganese-based material described in the present application.

[0015] As a fourth aspect of the present application, a battery is provided, comprising the positive electrode plate described in the present application.

[0016] Optionally, the battery includes a negative electrode plate, a separator, an electrolyte, and the positive electrode plate described in the present application.

[0017] As a fifth aspect of the present application, an electrical device is provided, which includes the battery described in the present application.

[0018] The present application prepares a modified lithium-rich manganese-based composite material by a combustion method, which is coated with a fast lithium ion conductor LiNbO3, and the core material is doped with Mg and Nb. The prepared lithium-rich manganese-based material can significantly improve the gram capacity of the battery at low temperature and the gram capacity at room temperature rate performance. At the same time, it can also improve the particle size, gram capacity and discharge efficiency of the lithium-rich manganese-based material, greatly improving the electrochemical performance of the battery. DETAILED DESCRIPTION

[0019] The present application discloses a lithium-rich manganese-based material and a preparation method thereof, as well as a positive electrode plate, a battery and an electrical device. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in this application. The products, processes and applications described in this application have been described through preferred embodiments. Relevant personnel can obviously modify or appropriately change and combine the products, processes and applications described in this article without departing from the content, spirit and scope of this application to realize and apply the technology of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0020] It should be noted that, in this article, if relational terms such as "first" and "second", "step 1" and "step 2", and "(1)" and "(2)" appear, they are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. At the same time, the embodiments in this application and the features in the embodiments may be combined with each other without conflict.

[0021] In order to improve the low-temperature performance gram capacity and room-temperature rate performance gram capacity of lithium-rich manganese-based positive electrode materials, the main strategy of this application is to improve the material by surface coating and ion doping of specific materials. The surface coating modification method adopts fast lithium ion conductor LiNbO3 coating, which mainly enhances the surface electron transport of the material and effectively reduces the side reactions between the material and the electrolyte. The ion doping modification method is mainly to improve the stability of the internal structure of the material, and the main doping sites are Li site and transition metal site (Ni site). Among them, Mg metal ions are selected as the doping element at the Li site, which can effectively improve the electronic conductivity; Nb metal ions are selected for doping at the transition metal Ni site to inhibit the mixed arrangement of Li and Ni, which can broaden Li + Transmission channels enhance the conductivity within the material lattice.

[0022] Based on the above technical ideas, in the first aspect of the present application, a lithium-rich manganese-based material is provided, which has a core-shell structure, and the core material includes a chemical formula of Li 1.2-x Mg x Ni 0.17-y Nb y Co 0.16 Mn 0.47 O2 material, x=0.05-0.1, y=0.05-0.07; shell material includes LiNbO3.

[0023] In some embodiments of the present application, x=0.05, 0.06, 0.07, 0.08, 0.09, or 0.1; y=0.05, 0.06, or 0.07; in some other embodiments of the present application, the core material is Li 1.15 Mg 0.05 Ni 0.12 Nb 0.05 Co 0.16 Mn 0.47 O2、Li 1.12 Mg 0.08 Ni 0.11 Nb 0.06 Co 0.16 Mn 0.47 O2、Li 1.1 Mg 0.1 Ni 0.1 Nb 0.07 Co 0.16 Mn 0.47 O2 one of them.

[0024] In certain embodiments of the present application, the shell material has a thickness of 2 to 6 nm; and the particle size of the lithium-rich manganese-based material is 500-800 nm.

[0025] In the process of preparing the lithium-rich manganese-based material, the present application adopts a combustion method, which not only has the advantages of fast heating speed and short reaction time, but also has a simple process, high efficiency and low equipment requirements. The production process can be easily completed by simply performing a thermal reaction in the air. All these characteristics show that the use of combustion synthesis is more advantageous than using traditional methods such as solid phase method, coprecipitation-sintering method, sol-gel method, and hydrothermal method to manufacture materials. Therefore, in the second aspect of the present application, a method for preparing the lithium-rich manganese-based material is provided, comprising:

[0026] The raw materials of lithium source, magnesium source, nickel source, first niobium source, cobalt source and manganese source are weighed according to the stoichiometric ratio of the core material, fuel is added and mixed evenly, and then high temperature treatment is performed to obtain a pre-burned product;

[0027] The pre-burned product is ball-milled with a raw material of a second niobium source dissolved in a solvent, dried, and then calcined at a high temperature to obtain the lithium-rich manganese-based material.

[0028] In certain embodiments of the present application, the lithium source includes one or more of lithium carbonate, lithium acetate, lithium nitrate, and hydrates thereof, such as LiC2H3O2·2H2O, etc.;

[0029] The magnesium source includes one or more of magnesium carbonate, magnesium hydroxide, magnesium acetate, magnesium nitrate, magnesium oxide, and hydrates thereof, such as Mg(NO3)2·4H2O, etc.;

[0030] The nickel source includes nickel acetate, nickel nitrate, nickel hydroxide, and one or more of their hydrates, such as Ni(NO3)2·4H2O, etc.;

[0031] The first niobium source and the second niobium source independently include niobium oxide, ammonium niobium oxalate, and one or more of their hydrates, such as Nb2O5, etc. In some embodiments of the present application, the first niobium source is niobium oxide, and the second niobium source is ammonium niobium oxalate;

[0032] The cobalt source includes cobalt acetate, cobalt nitrate, cobalt hydroxide, and one or more of their hydrates, such as CoC4H6O4·4H2O, etc.;

[0033] The manganese source includes one or more of manganese acetate, manganese nitrate, manganese hydroxide, and hydrates thereof, such as MnC4H6O4·4H2O.

[0034] In certain embodiments of the present application, the fuel includes urea, and the reference amount thereof is 50% of the total amount of metal ion substances in the raw materials. The raw materials of the lithium source, magnesium source, nickel source, first niobium source, cobalt source, and manganese source are mixed, ground with the fuel, and then subjected to high temperature treatment in a muffle furnace.

[0035] In certain embodiments of the present application, the high temperature treatment includes heat preservation treatment at 120-600°C; in other embodiments of the present application, after the raw materials are mixed, they are kept at 120-150°C for 1-3 hours, and then the temperature is increased to 550-600°C and kept for 3-5 hours, and the mixture burns due to the action of the fuel.

[0036] In certain embodiments of the present application, the solvent includes anhydrous ethanol. The second niobium source is dissolved and ball-milled with the pre-burned product, and then calcined at high temperature. In certain embodiments of the present application, the high-temperature calcination includes high-temperature calcination at 900-950° C. for 10-15 hours.

[0037] In the third aspect of the present application, a positive electrode sheet is provided, comprising the lithium-rich manganese-based material described in the present application. The lithium-rich manganese-based material can be directly pressed into a predetermined shape, such as a sheet, as a positive electrode sheet as needed; it can also be coated on at least one surface of a current collector to form a positive electrode sheet.

[0038] During the preparation of the positive electrode sheet, the lithium-rich manganese-based material is mixed with a conductive agent, a binder and a solvent to form a positive electrode slurry, and the positive electrode slurry is dried to obtain a positive electrode layer. In certain embodiments of the present application, the mass percentage of the lithium-rich manganese-based material: conductive agent: binder is 80-86%: 7-10%: 7-10%. Among them, the conductive agent includes but is not limited to one or more of carbon black conductive agents, graphene conductive agents and carbon fiber conductive agents. Carbon black conductive agents include conductive carbon black SP, Ketjen black and acetylene black, etc. The binders include PVDF, PAA, SBR, CMC, etc.

[0039] In a fourth aspect of the present application, a battery is provided, comprising the positive electrode sheet described in the present application, more specifically a lithium-ion battery comprising the positive electrode sheet described in the present application. The lithium-ion battery includes but is not limited to a soft-pack battery, a button battery, a square-shell battery, a half-battery or a full battery, etc.

[0040] In certain embodiments of the present application, the lithium-ion battery is a button cell, comprising a negative electrode plate, a separator, an electrolyte, and the positive electrode plate described in the present application. The negative electrode plate can be a metal lithium plate, and the separator and the electrolyte can be conventional materials.

[0041] In a fourth aspect of the present application, an electric device is provided, comprising the lithium-ion battery described in the present application, wherein the lithium-ion battery provides electric energy for the electric device. The electric device may be various devices or equipment driven by the lithium-ion battery, including but not limited to electric vehicles, electric vehicles, self-balancing vehicles, flatbed vehicles, aircraft, lighting equipment, household appliances, etc.

[0042] In each group of comparative experiments provided in this application, unless otherwise specified, other experimental conditions, materials, etc. are kept consistent except for the differences indicated in each group, so as to provide comparability. The experimental materials and reagents used in the examples can be obtained from commercial channels unless otherwise specified.

[0043] The following is a further description of a lithium-rich manganese-based material and a preparation method thereof, as well as a positive electrode plate, a battery and an electrical device provided in the present application.

[0044] Embodiment 1:

[0045] LiC2H3O2·2H2O(AR), Mg(NO3)2·4H2O(AR), Ni(NO3)2·4H2O(AR), Nb2O5(AR), CoC4H6O4·4H2O(AR), MnC4H6O4·4H2O(AR) raw materials are mixed in the ratio of 1.15mol Li∶0.05mol Mg∶0.12mol Ni∶0.05mol Nb∶0.16mol Co∶0.47mol Mn, and urea with a content of 50% of the total metal ion substance in the raw materials is used as fuel. The raw materials and fuel are mixed and ground for 1 hour. The ground mixture is placed in a muffle furnace and kept at 120℃ for 1 hour. The muffle furnace is heated to 600℃, and the mixture is burned immediately. It is kept at 600℃ for 5 hours. After the muffle furnace is cooled naturally, a mixture A is obtained, and the total weight of the mixture is 200g. In addition, 4 g of ammonium niobium oxalate was dissolved in anhydrous ethanol (AR) and the mixture A was high-speed ball-milled for 12 h in a ball mill with a revolution of 300 r / min and a rotation of 600 r / min, and dried at 80-110° C. The dried mixture was placed in a high-temperature furnace and calcined at 900° C. for 12 h in an air atmosphere to obtain a LiNbO3-coated, Mg- and Nb-doped lithium-rich manganese-based positive electrode material.

[0046] Embodiment 2:

[0047] Referring to the raw materials of Example 1, 1.12 mol Li: 0.08 mol Mg: 0.11 mol Ni: 0.06 mol Nb: 0.16 mol Co: 0.47 mol Mn were mixed in a ratio, and 50% urea of ​​the total amount of metal ions in the raw materials was used as fuel. The raw materials and the fuel were mixed and ground for 1 hour. The ground mixture was placed in a muffle furnace and kept at 120°C for 1 hour. The muffle furnace was heated to 600°C, and the mixture was burned immediately. It was kept at 600°C for 5 hours. After the muffle furnace was cooled naturally, a mixture A was obtained, and the total weight of the mixture was 200g. In addition, 4 g of ammonium niobium oxalate was dissolved in anhydrous ethanol (AR) and the mixture A was high-speed ball-milled for 12 h in a ball mill with a revolution of 300 r / min and a rotation of 600 r / min, and dried at 80-110° C. The dried mixture was placed in a high-temperature furnace and calcined at 900° C. for 12 h in an air atmosphere to obtain a LiNbO3-coated, Mg- and Nb-doped lithium-rich manganese-based positive electrode material.

[0048] Embodiment 3:

[0049] Referring to the raw materials of Example 1, 1.1 mol Li: 0.1 mol Mg: 0.1 mol Ni: 0.07 mol Nb: 0.16 mol Co: 0.47 mol Mn were mixed in a ratio, and 50% urea of ​​the total amount of metal ions in the raw materials was used as fuel. The raw materials and the fuel were mixed and ground for 1 hour. The ground mixture was placed in a muffle furnace and kept at 120°C for 1 hour. The muffle furnace was heated to 600°C, and the mixture was burned immediately. It was kept at 600°C for 5 hours. After the muffle furnace was cooled naturally, a mixture A was obtained, and the total weight of the mixture was 200g. In addition, 4 g of ammonium niobium oxalate was dissolved in anhydrous ethanol (AR) and the mixture A was high-speed ball-milled for 12 h in a ball mill with a revolution of 300 r / min and a rotation of 600 r / min, and dried at 80-110° C. The dried mixture was placed in a high-temperature furnace and calcined at 900° C. for 12 h in an air atmosphere to obtain a LiNbO3-coated, Mg- and Nb-doped lithium-rich manganese-based positive electrode material.

[0050] Comparative Example 1:

[0051] Referring to the raw materials of Example 1, 1.2 mol Li: 0 mol Mg: 0.17 mol Ni: 0 mol Nb: 0.16 mol Co: 0.47 mol Mn were mixed in a ratio, and 50% urea of ​​the total metal ion substance in the raw materials was used as fuel. The raw materials and the fuel were mixed and ground for 1 hour. The ground mixture was placed in a muffle furnace and kept at 120°C for 1 hour. The muffle furnace was heated to 600°C, and the mixture was burned immediately. It was kept at 600°C for 5 hours. After the muffle furnace was cooled naturally, a mixture A was obtained, and the total weight of the mixture was 200g. 4 g of ammonium niobium oxalate was dissolved in anhydrous ethanol (AR) and mixed with mixture A in a ball mill with a revolution of 300 r / min and a rotation of 600 r / min, and high-speed ball milled for 12 h, and dried at 80-110° C. The dried mixture was placed in a high-temperature furnace and calcined at 900° C. for 12 h in an air atmosphere to obtain a LiNbO3-coated, undoped lithium-rich manganese-based positive electrode material.

[0052] Comparative Example 2:

[0053] Referring to the raw materials of Example 1, the raw materials were mixed in a ratio of 1:15 mol Li: 0.05 mol Mg: 0.17 mol Ni: 0 mol Nb: 0.16 mol Co: 0.47 mol Mn, and urea, which was 50% of the total amount of metal ions in the raw materials, was used as fuel. The raw materials and the fuel were mixed and ground for 1 hour. The ground mixture was placed in a muffle furnace and kept at 120°C for 1 hour. The muffle furnace was heated to 600°C, and the mixture was burned immediately. It was kept at 600°C for 5 hours. After the muffle furnace was cooled naturally, a mixture A was obtained, and the total weight of the mixture was 200g. 4 g of ammonium niobium oxalate was dissolved in anhydrous ethanol (AR) and mixed with mixture A in a ball mill with a revolution of 300 r / min and a rotation of 600 r / min, and high-speed ball milled for 12 h, and dried at 80-110° C. The dried mixture was placed in a high-temperature furnace and calcined at 900° C. for 12 h in an air atmosphere to obtain a LiNbO3-coated, Mg-doped lithium-rich manganese-based positive electrode material.

[0054] Comparative Example 3:

[0055] Referring to the raw materials of Example 1, 1.2 mol Li: 0 mol Mg: 0.12 mol Ni: 0.05 mol Nb: 0.16 mol Co: 0.47 mol Mn were mixed in a ratio, and 50% urea of ​​the total metal ion substance in the raw materials was used as fuel. The raw materials and the fuel were mixed and ground for 1 hour. The ground mixture was placed in a muffle furnace and kept at 120°C for 1 hour. The muffle furnace was heated to 600°C, and the mixture was burned immediately. It was kept at 600°C for 5 hours. After the muffle furnace was cooled naturally, a mixture A was obtained, and the total weight of the mixture was 200g. In addition, 4 g of ammonium niobium oxalate was dissolved in anhydrous ethanol (AR) and mixed with mixture A in a ball mill with a revolution of 300 r / min and a rotation of 600 r / min, and high-speed ball milled for 12 h, and dried at 80-110° C. The dried mixture was placed in a high-temperature furnace and calcined at 900° C. for 12 h in an air atmosphere to obtain a lithium-rich manganese-based positive electrode material coated with LiNbO3 and doped with only Nb.

[0056] Experimental example:

[0057] 1. Battery assembly

[0058] The lithium-rich manganese-based material, the conductive agent SP, PVDF and NMP are stirred and mixed to obtain a positive electrode slurry; wherein the lithium-rich manganese-based material: the conductive agent: the binder = 80:10:10. The positive electrode material is dried under vacuum, and the dried positive electrode material is pressed into a sheet, and the thickness of the sheet positive electrode material is less than 0.3 mm; specifically, the sheet positive electrode material, the metal lithium sheet, the separator, and the electrolyte are assembled into a button battery CR2032 for charge and discharge experiments.

[0059] 2. Detection method:

[0060] (1) The particle size of the material was counted using a Malvern laser particle size analyzer; the gram capacity of the material was obtained by assembling a CR2032 battery and charging and discharging it at room temperature at a constant current of 0.1C, and the discharge / charge efficiency was further calculated;

[0061] (2) Low temperature test: The assembled CR2032 battery was first charged and discharged for 3 cycles at room temperature at a constant current of 0.5C, and the average value was taken as the initial value; then it was placed at 0℃, -10℃, and -20℃ for 24h, and the charge and discharge cut-off voltage was 2.0~4.8V (vs.Li / Li + ), and then 0.5C charge and discharge are performed to obtain the gram capacity of the battery material.

[0062] Rate test: The assembled CR2032 battery was subjected to 0.5C, 1C, 2C, and 5C constant current charge and discharge curves in sequence.

[0063] 3. Test results

[0064] Table 1 Particle size, gram capacity and discharge efficiency of each group of lithium-rich manganese-based materials

[0065]

[0066] According to Table 1, compared with the embodiment, the comparative examples are lithium-rich manganese-based materials without doping and doping with only one metal ion. From the perspective of particle size, the particle size of the comparative examples is reduced as a whole; at the same time, there are also different degrees of decreases in 0.1C gram capacity and 0.1C discharge efficiency, showing a decrease in performance. This shows that the lithium-rich manganese-based material prepared in this application has a certain improvement in electrochemical performance.

[0067] Table 2 Capacity (mAh / g) of each group at low temperature and rate performance

[0068]

[0069]

[0070] It can be clearly seen from Table 2 that the lithium-rich manganese-based material of the present application can maintain a relatively high gram capacity in a low temperature environment, avoid the occurrence of attenuation in the comparative example, and ensure that the battery has a relatively high electrochemical performance level; and during the room temperature rate performance test, the gram capacity under different test conditions is also significantly higher than that of each comparative example, also showing excellent electrochemical performance.

[0071] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A lithium-rich manganese-based material, characterized in that: It has a core-shell structure, and the core material includes a chemical formula of Li 1.2- x Mg x Ni 0.17-y Nb y Co 0.16 Mn 0.47 O2 material, x=0.05-0.1, y=0.05-0.07; shell material includes LiNbO3.

2. The lithium-rich manganese-based material according to claim 1, characterized in that The shell material has a thickness of 2-6 nm.

3. The method for preparing the lithium-rich manganese-based material according to claim 1, characterized in that: include: The raw materials of lithium source, magnesium source, nickel source, first niobium source, cobalt source and manganese source are weighed according to the stoichiometric ratio of the core material, fuel is added and mixed evenly, and then high temperature treatment is performed to obtain a pre-burned product; The pre-burned product is ball-milled with a raw material of a second niobium source dissolved in a solvent, dried, and then calcined at a high temperature to obtain the lithium-rich manganese-based material.

4. The preparation method according to claim 3, characterized in that: The lithium source includes lithium carbonate, lithium acetate, lithium nitrate, and one or more of their hydrates; the magnesium source includes magnesium carbonate, magnesium hydroxide, magnesium acetate, magnesium nitrate, magnesium oxide, and one or more of their hydrates; the nickel source includes nickel acetate, nickel nitrate, nickel hydroxide, and one or more of their hydrates; the first niobium source and the second niobium source independently include niobium oxide, ammonium niobium oxalate, and one or more of their hydrates; the cobalt source includes cobalt acetate, cobalt nitrate, cobalt hydroxide, and one or more of their hydrates; the manganese source includes manganese acetate, manganese nitrate, manganese hydroxide, and one or more of their hydrates.

5. The preparation method according to claim 3, characterized in that: The fuel includes urea.

6. The preparation method according to claim 3, characterized in that: The high temperature treatment includes heat preservation treatment at 120-600°C; the high temperature calcination includes high temperature calcination at 900-950°C.

7. A positive electrode sheet, characterized in that: Including the lithium-rich manganese-based material according to claim 1 or 2.

8. A battery, characterized in that: Including the positive electrode sheet as described in claim 7.

9. The battery according to claim 8, characterized in that It comprises a negative electrode plate, a separator, an electrolyte, and the positive electrode plate as claimed in claim 7.

10. An electrical device, characterized in that: A battery comprising the battery of claim 8 or 9.